A dynamic view of job satisfaction in psychiatric nurses in Germany - Büssing, André [Verfasser] (My University, 1992)
"The autor criticizes static attitude measurement of job satisfaction because of its artificial results: chiefly the high proportion of satisfied persons. A model of different forms of job satisfaction proposed by Bruggemann is introduced to overcome this problem. It is a dynamic model consisting of three basic variables: comparison between actual value of the work situation and nominal value of the person, changes in level of aspiration, and problem- solving behaviour (coping). The model predicts forms instead of degrees of job satisfaction whereby the six forms: progressive, stabilized, resigned, pseudo-job satisfaction, and fixated as well as constructive job dissatisfaction are differentiated. Research performed with this model is summarized and evaluated. Two studies with psychiatric nurses (n=72; n=232) are presented; both use a questionnaire (AZK) to measure different forms of job satisfaction. Cluster analyses and subsequent discriminant analyses were calculated to generate forms. Results partly confirm the predictions; several clusters cannot be interpreted by pure forms of job satisfaction; they have to be interpreted by mixed forms of job satisfaction. In both studies about 40% of the satisfied nurses are actually resigned satisfied. To investigate the relations between control at work and forms of job satisfaction, comparisons are made between three forms - resigned job satisfaction, constructive job satisfaction, and constructive job dissatisfaction - with respect to six aspects of control at work. Results confirm the close relationships hypothesized. Critical aspects of the model, possibilities of further research, and consequences for studies in organizations, especially hospitals, are discussed with respect to performance, quality of care and intervention." (author's abstract) ((en)) Der Autor kritisiert statische Messungen der Berufszufriedenheit, da sie häufig zu überhöhten positiven Resultaten führen. Als Alternative schlägt er ein dynamisches Modell mit sechs differenzierten Formen der Berufszufriedenheit vor. (IAB)
Eine dynamische Betrachtung der Arbeitszufriedenheit bei Krankenschwestern in der deutschen Psychiatrie
Keywords: S 6.4.5.2 Übrige Gesundheitsberufe (außer Ärzte und Apotheker); G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 2.4.4 Biografiegestaltung; G 2.3 Wandel von Arbeit & Wirtschaft; P 1.3 Frauen; Messung; Krankenschwester; Care work; Berufsproblem; Berufszufriedenheit; Modell; Frauen in Einzelberufen; Frauenarbeit; Quantitative Angaben